Seasons of Grace A History of the Catholic Archdiocese of Detroit - Woodcock Tentler, Leslie (Wayne State University Press, 2018)
Seasons of Grace is a history of the Catholic Church and community in southern lower Michigan from the 1830s through the 1950s. More than a chronicle of clerical successions and institutional expansion, the book also examines those social and cultural influences that affected the development of the Catholic community. To document the course of institutional growth in the diocese, Tentler devotes a portion of the book to tracing the evolution of administrative structures at the Chancery and the founding of parishes, parochial schools, and social welfare organizations. Substantial attention is also given to the social history of the Catholic community, reflected in changes in religious practice, parish life and governance, and the role of women in church organizations and in devotional activities. Tentler also discusses the issue of Catholics in state and local politics and Catholic practice with regard to abortion, contraception, and intermarriage.